THE DEVELOPMENT OF ENGLISH READING COMPREHENSION BASED ON CONSTRUCTIVISM OF GRADE 3 STUDENTS - Sonkhunthod, Nisarad; Prommuang, Pinyo (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The purposes of this research were: 1) to test English reading skills for pre-school and post-study understanding by managing constructivist theory learning. My family grade 3 2) to compare English reading skills for understanding by managing constructivist theory learning. My family grade 3 after studying with 70 percent criteria 3) to study the satisfaction of third graders towards constructivist theory learning management. The samples used in the research were 24 third-graders who were studying in second semester of the academic year 2021. Ban Lung School (Maiuraphakhom). Nakhon Ratchasima Primary Educational Service Area Office 5 1) Constructivist Theory Learning Management Plan. 2) Reading proficiency test for English comprehension the statistics used in the analysis include percentage, average, standard deviation, hypothesis test using Wilcoxon Signed Ranks Test 3) student satisfaction test for teaching activities for understanding constructive English. The research findings were as follows: 1) The student learning achievement in English reading for understanding by learning management According to constructivist theory. My family grade 3 was higher than before students’ studying at the 0.05 level. 2) The student learning achievement in English reading development for understanding by managing constructivist learning. My family grade 3 was statistically significantly at the .05 level. 3) A test of student’ opinions toward teaching activities for understanding English based on constructivist theory, as a whole, the attitude toward English at a high level.